GE_GERICHTE C/3282/2014 vom 12. Juni 2015 - GE Cour de justice (2015)
USAGE COMMERCIAL ; ANNULABILITÉ; RÉSILIATION ; CHANGEMENT D'AFFECTATION ; LOGEMENT ; PROLONGATION DU BAIL À LOYER ; RÉCUSATION | CPC.47; CO.271; LTR.7; CO.272;